Analysis of visual evoked potentials in patients with neurofibromatosis type 1: new concepts - Jancic, Jasna; Zarkovic, Nikola; Nikolic, Blazo; Ivancevic, Nikola; Rovcanin, Branislav; Nesic, Dejan (Frontiers in Neurology, 2024)
Neurofibromatosis type 1 (NF type 1) is an autosomal dominant disease with typical clinical manifestations, such as skin lesions, Lisch nodules, optic pathway gliomas, and neurofibromas, caused by the mutation of the NF1 gene. Visual evoked potentials (VEP) present a measure of the electrophysiological response of visual cortex to a visual stimulus. The role of VEP in the pathophysiology of NF type 1 is very complex and requires additional research.The Aim: We examined the differences between NF type 1 patients with normal and altered VEP and analyzed the correlation between the prolongation of P100 latency and disease severity.Material and methods: Two groups were formed: a control group and a study group with NF type 1 patients. Based on the control group analysis, a threshold value for a normal VEP finding of 116ms was obtained, and it was used to divide the study group into subgroups with normal and altered VEP. We proceeded with examining the differences in clinical manifestations of the disease between the subgroups, after which we checked if there is a correlation between the prolongation of the P100 latency and the severity of the clinical picture according to the Riccardi scale. Statistical analysis was performed using the Pearson chi-square test and the Spearman correlation test in the program SPSS 28.0, with levels of statistical significance p=0.05 and p=0.001.In the group with the abnormal VEP we found a statistically significant more frequent occurrence of optic tract glioma (p=0.008), tumors (p=0.032), epilepsy (p=0.043), and cognitive disorders (p=0.028), while the other clinical signs had an equal prevalence in both groups. A moderately strong correlation (rs=0.665) was observed between the prolongation of P100 latency and the severity of the clinical picture. Conclusion: Our results showed the important role of VEP in the description of clinical phenotypes of NF type 1. The authors of the study propose VEP to be included in the diagnostic algorithms designed for patients with NF type 1.